Exploring criminal and illegal enterprise new perspectives on research, policy & practice - McElwee, Gerard; Smith, Robert (Emerald, 2015)
This book examines the illegal behaviour of entrepreneurs and discusses how criminal entrepreneurs acquire information, learn from their entrepreneurial experiences, and utilize acquired knowledge to develop their organizations. The chapters demonstrate several dimensions of the entrepreneurial processes, such as imagination, innovation, calculated risk taking, alertness to opportunities, opportunity identification, as well as resource assemblage and leverage to exploit an opportunity - all in a criminal context. Illegal methods used by entrepreneurs to identify solutions to problems that lead to the generation of business opportunities are illustrated. Moreover, methods used by criminal entrepreneurs to circumvent barriers to the entrepreneurial process and business developments are highlighted. Issues relating to the formation of crimino-entrepreneurial ventures are critically discussed. Emerging issues relating to illegal corporate entrepreneurship are illustrated.
Keywords: Organized crime.; Entrepreneurship.; Business enterprises -- Corrupt practices.; elektronické knihy; electronic books